Educational Space in Inclusiv Education - Challenges in Working witha Diverse Group/Class - Iwona Bożena Chrzanowska (Maria Curie-Skłodowska University, Lublin, Poland, 2024)
Introduction: Nowadays, teachers must be aware that the student population in school classes is becoming increasingly diverse. Therefore, it is necessary to design educational spaces that not only cater to the diverse needs of students but also align with the requirements of the 21st century. Research Aim: This research seeks to investigate the importance of educational spaces when working with a diverse group or class in inclusive education. The research question focuses on understanding how to design, why to change educational spaces in education. Evidence-based Facts: The educational environment can play the role of the "third teacher" and either support or hinder the development of students. Engaging educational environments are crucial for the cognitive, physical, social, and emotional development of students. They promote critical thinking, communication, collaboration, and creativity, all of which are considered essential competencies in 21st-century education. Summary: Diverse student needs require diverse learning spaces to meet the requirements and address the needs of every student. These spaces are often described using metaphors like a watering hole, cave, campfire, or laboratory. Students should be involved in the creation of educational spaces. However, students' perspectives are frequently overlooked. Research findings indicate that considering their input enhances the likelihood of providing better and more effective support for their development. In traditional education, teachers play a central role in selecting teaching methods and determining modes of school communication. There are already examples of how to transform a school's environment to make it inclusive for everyone.